AL-QURAN TRANSLATION APPLICATIONS USING MICROSOFT ACCESS - Kusma Miretna; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2006)
This writing describes the application of the Quran translation, namely how to displaythe translation of Al Quran in Indonesian, looking for a letter in the Qur'an and itsverses quickly and find a word in the Qur'an along with the number of verses thathave the word, so that the younger generations with quickly and easily understand thecontents of the Qur'an along with the development of an increasingly technologicalprogress. This application uses Microsoft Access to operate. Besides easy, thisapplication is also very interesting because it comes with the images that supports theapplication.